Regioselective C(sp3)–H amidation of 8-methylquinolines with N-hydroxyphthalimides. Issue 94 (9th November 2022) - Kumar, Rohit; Parmar, Diksha; Chandra, Devesh; Sarthi,; Sharma, Upendra
Abstract : Herein, the Rh(iii )-catalysed C(sp 3 )–H bond amidation of 8-methylquinolines using N -hydroxyphthalimides as the amidation source is explored. Abstract : Herein, the Rh(iii )-catalysed C(sp 3 )–H bond amidation of 8-methylquinolines using N -hydroxyphthalimides as the amidation source is explored. Diversely substituted 8-methylquinolines were well tolerated and furnished the amidated products in excellent yields with high regioselectivity. The developed reaction conditions were also applied successfully for the secondary C(sp 3 )–H amidation of 8-ethylquinolines. Besides that, the reaction is also applicable for the gram-scale synthesis of the amidated product. In addition, the late-stage amidation of santonin oxime as well as carvone oxime and the diversification of the amidated product was also carried out to illustrate the relevance of the developed methodology. Mechanistic studies revealed that the current reaction proceeds through a five-membered rhodacycle intermediate and does not involve the radical pathway.